1998
DOI: 10.1021/jf970585p
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant Delphinium Diterpenoid Alkaloids. Structure−Activity Relationships

Abstract: The insect antifeedant and toxic activity of the Delphinium diterpene alkaloids 15-acetylcardiopetamine, cardiopetamine along with its amino alcohol, the beta,gamma unsaturated ketone, and the acetylated ketone derivatives were studied in Spodoptera littoralis and Leptinotarsadecemlineata. Cardiopetamine and 15-acetylcardiopetamine strongly inhibited the feeding activity of S. littoralis and L. decemlineata, respectively. Structure-activity studies with S. littoralis showed that the C13 and C15 hydroxy substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 35 publications
2
36
0
1
Order By: Relevance
“…In this article, we present a comparative overview of the insecticidal effects (antifeedant and toxic) on Spodoptera littoralis and Leptinotarsa decemlineata, the cytotoxicity on several tumoral cell lines with varying multidrug resistance mechanisms (CT26, SW480, HeLa, SkMel25 and SkMel28), and the antiparasitic effects against Trypanososma cruzi and Leishmania infantum of 67 diterpenoid alkaloids (44 NDAs, and 23 DAs) from several chemical classes (Gonzá lez-Coloma et al 1998, 2004aGonzá lez et al 2005Gonzá lez et al , 2006De Iné s et al 2006), isolated from Aconitum, Delphinium and Consolida species (citations in Gonzá lez-Coloma et al 1998, 2004aDe la Fuente and Reina 1990). …”
Section: Introductionmentioning
confidence: 99%
“…In this article, we present a comparative overview of the insecticidal effects (antifeedant and toxic) on Spodoptera littoralis and Leptinotarsa decemlineata, the cytotoxicity on several tumoral cell lines with varying multidrug resistance mechanisms (CT26, SW480, HeLa, SkMel25 and SkMel28), and the antiparasitic effects against Trypanososma cruzi and Leishmania infantum of 67 diterpenoid alkaloids (44 NDAs, and 23 DAs) from several chemical classes (Gonzá lez-Coloma et al 1998, 2004aGonzá lez et al 2005Gonzá lez et al , 2006De Iné s et al 2006), isolated from Aconitum, Delphinium and Consolida species (citations in Gonzá lez-Coloma et al 1998, 2004aDe la Fuente and Reina 1990). …”
Section: Introductionmentioning
confidence: 99%
“…The insecticidal and anti-feedant activity of NDAs [8][9][10], suggest a defensive role played by these compounds. However, only a few DAs have been studied for their plant defensive and pharmacological properties, including their effects on Trypanosoma cruzi epimastigote forms [9,[11][12][13][14][15] and their neurotoxic effects are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 20, a rearranged hetisine with an adamantane-type skeleton, was the strongest CPB antifeedant tested here. Previous studies have shown that the S. littoralis antifeedant effects of several hetisine-type DAs, including 2 ± 6, depended on the OH group at C(13) and C (15), while the presence of a OH group at C(13) and/or of a AcO group at C(15) affected their activity on CPB [10]. Furthermore, the potency as antiplatelet aggregation agents of several atisine-type DAs was closely affected by the presence of an O-substitution at C(15) [11].…”
mentioning
confidence: 97%